RELATIONSHIP OF BREASTFEEDING WITH GROSS AND FINE MOTOR SKILLS DEVELOPMENT IN INFANT 6-12 MONTHS - Rukanah, Rukanah (Journal of Vocational Nursing, 2021)
Introduction: WHO recommends exclusive breastfeeding for newborn sup to six month sofage. Exclusive breastfeeding is given forinfantonlybreastmilk, not given food or other fluids, evenwater, except for vitamins, minerals, ormedicines. Exclusive breast feeding has a positive effect on the motor development of infants in earlylife. This study aimed to determine the relationship between breastfeeding with gross and fine motor skills development in infants 6-12 months. Methods: The design was a cross-sectional study, a total sample of 43 infants with a simple random sampling technique. The research instrument used questionnaires and interviews to obtain data on exclusive breastfeeding, to measure gross motor and fine motor skills development using a checklist form based on Denver II. Data analysis used the Chi-square test with a significance level of α <0.05. Results: The results showed a significant relationship between breastfeeding and gross motor skills development in infants (p=0,000), and there was no relationship between breastfeeding and fine motor skills development in infants (p=0,191). Conclusion: The study concludes that there is the level of knowledge and readiness of mothers in giving exclusive breastfeeding was still lacking and it could cause gross motor skills in infants to experience delays, although not significantly. By providing breastfeeding, it can provide many benefits for mothers and babies, so it is hoped that mothers will increase their knowledge about giving breastfeeding exclusively and implementing it.